Testing a rational choice model of “desistance:”: decomposing changing expectations and changing utilities - Thomas, Kyle J. (Criminology, 2019)
We argue that a rational choice framework can be used to explain declines in offending from adolescence to young adulthood in two ways. First, subjective expectations of offending can be age graded such that perceptions of rewards decrease and perceptions of risks and costs increase. Second, the marginal (dis)utility of crime may be age graded (e.g., preferences for risks, costs, and rewards). We examine changes in offending from adolescence to young adulthood among a subset of individuals from the Pathways to Desistance Study (N = 585) and employ a nonlinear decomposition model to partition differences in offending attributable to changing subjective expectations (X) and changing marginal utilities (β). The results indicate that both have direct and independent effects on changes in offending over time. The results of a detailed decomposition on the subjective expectations also indicate that differences exist across the type of incentives. That is, the effect of changing expectations is attributed mainly to changes in perceived rewards (both social and intrinsic). Changing expectations of social costs and risk of arrest from offending have weak effects on changes in criminal behavior, which suggests that they must be accompanied by increases in the weight placed on these expectations to promote appreciable declines in offending.